Empirical Analysis of the Impact of Taxation Policy on the interest of Corporate Sharia Sukuk issuance in Indonesia Perspective of SBSN National Sharia Securities Law - Putri Rahmawati, Shelly; Isman; Budiman, Mamdukh (Qawanin: Jurnal of Economic Syaria Law, 2025)
This study aims to empirically analyze the effect of taxation policy as stipulated in the State Sharia Securities Law (SBSNLaw) on the interest in corporate sharia sukuk issuance in Indonesia. With a quantitative approach and multiple linear regression method, this study uses secondary data from official publications of financial authorities and capital markets. The results of the analysis show that taxation policy has a significant influence on interest in sukuk issuance, with a coefficient of determination (R²) of 0.82, which means that 82% of the variation in interest in issuance can be explained by taxation variables. This finding indicates that tax incentives, final income tax exemptions, and fiscal treatment of sharia contracts are key factors in encouraging corporate decisions to issue sukuk. In addition, there is a seasonal pattern of sukuk issuance that stands out in the second and fourth quarters. This research provides practical implications for policymakers to strengthen the effectiveness of the SBSN Law through improving incentive schemes and paying attention to market momentum in encouraging the growth of Islamic sukuk as a sustainable financing instrument.